Criterion for dynamical instability of mass transfer in binary evolution - Han, Z; Podsiadlowski, P; Tout, C (2002)
Using Eggleton's code, we performed a series of binary evolution calculations in order to investigate the criterion for dynamical instability of mass transfer in binaries. In these calculations; we took the donor's mass on the zero-age main sequence (ZAMS) from 0.8 to 1.9 MD. For each mass, we systematically varied the mass of the core at the beginning of mass transfer and the mass of the companion star. We assumed that mass transfer was completely non-conservative and that all the mass that was lost from the system carried with it the orbital angular momentum of the accreting component. We found that the critical mass ratio, above which mass transfer is dynamically unstable, is from 1.1 to 1.3 in these red-giant binary systems.